Hypereutectic Al-Si alloy, hypereutectic Al-Si alloy casting and manufacturing method thereof

JP7652680B2Active Publication Date: 2025-03-27NIPPON LIGHT METAL CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021181160
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-11-05
Publication Date
2025-03-27
Estimated Expiration
2041-11-05

Smart Images

  • Figure 0007652680000002
    Figure 0007652680000002
  • Figure 0007652680000003
    Figure 0007652680000003
  • Figure 0007652680000001
    Figure 0007652680000001
Patent Text Reader

Abstract

To provide a hypereutectic Al-Si alloy casting that is allowed to express a linear expansion coefficient lower than or equal to 17×10-6°C-1 without a significant increase in Si content and in a simple and inexpensive manner, and a hypereutectic Al-Si alloy suitable for the hypereutectic Al-Si alloy casting, and a simple and efficient production method for the hypereutectic Al-Si alloy casting.SOLUTION: A hypereutectic Al-Si alloy comprises Si: 15.0-17.0 wt.%, Ni: 3.0-5.0 wt.%, and P: 5-50 ppm, with the balance being Al and unavoidable impurities.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a hypereutectic Al-Si alloy for obtaining a hypereutectic Al-Si alloy casting having a low linear expansion coefficient, a hypereutectic Al-Si alloy casting having a low linear expansion coefficient, and a method for producing the same. [Background technology]

[0002] Aluminum (Al) is a metal with a high linear expansion coefficient compared to other materials such as iron (Fe) and ceramics, but a low linear expansion coefficient is required for various machine parts that require high dimensional accuracy and are subject to large temperature changes, such as engine cylinder liners, VTR cylinders, engine pistons, compressor vanes, etc. Also, when used in conjunction with other materials, aluminum alloys with a low linear expansion coefficient are often required.

[0003] In order to reduce the linear expansion coefficient of aluminum, a method has been used in which Si is added in an amount greater than the eutectic composition to crystallize primary Si as a hypereutectic Al-Si alloy. However, this method requires the addition of a large amount of Si to reduce the linear expansion coefficient of aluminum, and when the Si content is 20 mass% or more, it becomes difficult to cast the Al-Si alloy.

[0004] For example, in Patent Document 1 (JP 2009-263720 A), for the purpose of obtaining an aluminum alloy sheet material having a low linear thermal expansion coefficient and high yield strength, an aluminum alloy sheet material containing 11.0 to 15.0 mass% Si, 0.3 to 1.0 mass% Mg, 0.001 to 0.02 mass% in total of one or two of P and Sr, and 0.005 to 0.15 mass% Ti or 0.005 to 0.15 mass% Ti and 0.0005 to 0.05 mass% B, with the remainder being Al and unavoidable impurities, has an average linear expansion coefficient in the range of room temperature to 100° C. of 21×10 -6 / ℃ or less, room temperature strength: 280N / mm 2 An aluminum alloy sheet material having excellent yield strength and low thermal expansion, characterized by the above-mentioned, has been proposed.

[0005] In the low-thermal expansion aluminum alloy sheet material described in Patent Document 1, the Si content is reduced, the Mg content is 0.3 to 1.0 mass %, and the Cu content is within the impurity range. The alloy ingot can be rolled into a plate material having a thickness of about 2.5 mm without concerns about edge cracks or plate breakage during plate rolling, and the combination of heat treatment and cold rolling gives it high yield strength, and the linear expansion coefficient can be reduced in the range of room temperature to 100°C by selecting the composition.

[0006] Furthermore, Patent Document 2 (JP Patent Publication 62-056551 A) proposes an aluminum alloy material having a low linear expansion coefficient and a strength comparable to that of conventional heat-resistant aluminum alloys for forging. The aluminum alloy material has a low linear expansion coefficient and is characterized in that it is an extruded or forged material made of rapidly solidified aluminum alloy powder having a chemical composition by weight of 17-27% Si, 2-10% Mg, and the remainder being substantially Al, and that fine-grained eutectic Si is uniformly dispersed in an Al solid solution in which Si and Mg are supersaturated in the Al matrix.

[0007] The Al alloy material described in the above Patent Document 2 contains 15 to 25% Si, and in combination with the addition of Mg, the linear expansion coefficient is reduced by about 20% at 300°C or less compared to conventional Al alloys for forging. In addition, a large amount of eutectic Si, which does not deteriorate mechanical properties, is uniformly dispersed in the Al solid solution in the form of fine particles, so that good wear resistance can be imparted without any deterioration in mechanical properties. In addition, since the material contains 2 to 10% Mg, the matrix is ​​supersaturated with Mg and solid-solution hardening is achieved, which is said to contribute to improving strength and reducing the linear expansion coefficient by preventing dislocations. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2009-263720 A [Patent Document 2] Japanese Patent Application Publication No. 62-056551 Summary of the Invention [Problem to be solved by the invention]

[0009] The low-thermal expansion aluminum alloy sheet material described in Patent Document 1 has both a low linear expansion coefficient and high yield strength, but in recent years, there has been a strong demand for an even lower linear expansion coefficient. In addition, the Al alloy material described in Patent Document 2 has an extremely high Si content, is an extruded material or forged material of rapidly solidified Al alloy powder, and is obtained by uniformly dispersing mainly fine-grained eutectic Si in an Al solid solution in which Si and Mg are supersaturated in an Al matrix, and the members to which it can be applied are limited in terms of raw materials, manufacturing process, and manufacturing costs.

[0010] In order to reduce the linear expansion coefficient of aluminum by using primary silicon, it is necessary to add a certain amount of silicon. -6 ℃ -1 The following linear expansion coefficient is required, and in order to obtain an aluminum alloy with this thermal expansion coefficient, it is necessary to add 20 mass% or more of Si. However, if the Si content is 20 mass% or more, it becomes difficult to cast the Al-Si alloy.

[0011] In addition, the addition of a large amount of Si makes it easier for coarse primary Si crystals to form, which makes casting defects more likely to occur. Furthermore, the coarse primary Si crystals become the starting point of fracture when a large external stress is applied, which causes a decrease in toughness. Furthermore, a large amount of primary Si crystals may cause wear of cutting tools and deterioration of the surface properties of the casting.

[0012] In view of the above problems in the prior art, the object of the present invention is to provide a method for easily and inexpensively producing a 17×10 -6 ℃ -1 The present invention provides a hypereutectic Al-Si alloy casting capable of exhibiting the following linear expansion coefficient, a hypereutectic Al-Si alloy that can be suitably used for the hypereutectic Al-Si alloy casting, and a simple and efficient method for producing the hypereutectic Al-Si alloy casting. [Means for solving the problem]

[0013] In order to achieve the above object, the present inventors have conducted extensive research into the composition of hypereutectic Al-Si alloys, the relationship between the microstructure and linear expansion coefficient of hypereutectic Al-Si alloy castings, and the manufacturing method of hypereutectic Al-Si alloy castings. As a result, they have discovered that adding appropriate amounts of P and Ni to a hypereutectic Al-Si alloy, holding a molten aluminum alloy having the composition at a temperature of 1050°C and then casting it is extremely effective in refining the primary Si crystals in the hypereutectic Al-Si alloy castings and reducing the average spacing between adjacent eutectic Si crystals, and have arrived at the present invention.

[0014] That is, the present invention provides: Si: 15.0-17.0wt%, Ni: 3.0-5.0wt%, P: 5 to 50 ppm, The balance is Al and unavoidable impurities. The present invention provides a hypereutectic Al-Si alloy, characterized in that:

[0015] In the hypereutectic Al-Si alloy of the present invention, by containing 5 ppm or more of P, a large number of AlP compounds that become the nuclei of primary crystal Si during melting and solidification are formed, and a large number of fine primary crystal Si are formed at the same time, thereby suppressing the coarsening of primary crystal Si. On the other hand, by making the P content 50 ppm or less, the number of AlP compounds does not become too large, and the formed AlP compounds are consumed by primary crystal Si, so that they hardly exist during eutectic solidification. As a result, the residual liquid is supercooled during eutectic solidification, and the coarsening of the eutectic is suppressed by shortening the solidification time. In order to refine primary crystal Si and eutectic Si using these mechanisms, it is preferable to make the P content 20 to 40 ppm.

[0016] In addition, in the hypereutectic Al-Si alloy of the present invention, by containing 3.0wt% or more of Ni, Al-Ni compounds are crystallized, and the linear expansion coefficient can be reduced by extremely efficiently dividing the α phase. In addition, by making the Ni content 5.0wt% or less, it is possible to suppress the deterioration of the toughness of the hypereutectic Al-Si alloy casting due to the coarsening of the Al-Ni compounds.

[0017] Generally, it is said that the linear expansion coefficient of a metal material is greatly influenced by its composition. However, the reduction in the linear expansion coefficient by finely dividing the α phase is a phenomenon discovered for the first time by the present inventors, and the present invention was made based on this phenomenon.

[0018] The present invention also provides a method for producing a method for manufacturing a semiconductor device comprising the steps of: The hypereutectic Al-Si alloy of the present invention is The average grain size (equivalent circle diameter) of primary crystal Si is 40 μm or less, The average spacing between adjacent eutectic Si is 20 μm or less, Linear expansion coefficient is 17 x 10 -6 ℃ -1 That is: The present invention also provides a hypereutectic Al-Si alloy casting, characterized by:

[0019] The hypereutectic Al-Si alloy casting of the present invention has an average grain size (equivalent circle diameter) of primary Si crystals of 40 μm or less, and the α-phase is divided by the dispersion of fine primary Si crystals, resulting in a low linear expansion coefficient. In addition, since it does not contain coarse primary Si crystals, the decrease in tensile strength and elongation caused by the primary Si crystals becoming the starting point of fracture when stress is applied is suppressed.

[0020] In addition, the hypereutectic Al-Si alloy casting of the present invention has an average spacing between adjacent eutectic Si of 20 μm or less, which effectively divides the α phase and reduces the linear expansion coefficient. In addition, the refinement of the eutectic Si suppresses the decrease in tensile strength and elongation caused by the eutectic Si becoming the origin of fracture when stress is applied.

[0021] The hypereutectic Al-Si alloy casting of the present invention has a linear expansion coefficient of 17×10 due to the division of the α phase by primary crystal Si and eutectic Si. -6 ℃ -1 The linear expansion coefficient is 16.8×10 -6 ℃ -1 It is preferable that the value is less than 16.5×10 -6 ℃ -1 It is more preferable that the coefficient of linear expansion is not more than 1. Here, the "coefficient of linear expansion" in the present invention means the average coefficient of linear expansion at 30 to 150°C.

[0022] In addition, the hypereutectic Al-Si alloy casting of the present invention preferably contains Al3Ni crystallized. For example, compared with Al3Ni2 crystallized in an Al-Ni-Cu aluminum alloy, Al3Ni crystallized matter tends to have a larger aspect ratio and can effectively divide the α phase.

[0023] Furthermore, the present invention provides The molten aluminum alloy made of the hypereutectic Al-Si alloy of the present invention is held at a temperature of 1050°C or higher for 5 minutes or more, and then cast. Also provided is a method for producing a hypereutectic Al-Si alloy casting, characterized by:

[0024] The hypereutectic Al-Si alloy used in the method for producing hypereutectic Al-Si alloy castings of the present invention contains 5 to 50 ppm of P, which exists as AlP compounds, but the AlP compounds are dissolved by heating the molten hypereutectic Al-Si alloy to 1050°C or higher, which is the crystallization temperature of the AlP compounds or higher (molten metal superheating treatment). When the AlP compounds are subsequently resolidified, they become smaller than before they were melted, and a large amount of fine AlP compounds are dispersed.

[0025] Here, the fine AlP compounds become the nuclei for the formation of primary crystal Si, and the coarsening of primary crystal Si is suppressed by the simultaneous formation of many fine primary crystal Si. On the other hand, the content of P is 50 ppm or less, so that the number of AlP compounds is not too large, and the formed AlP compounds are consumed by primary crystal Si, so that they are hardly present during eutectic solidification. As a result, the residual liquid during eutectic solidification is supercooled, and the solidification time is shortened, so that the coarsening of eutectic Si is suppressed. That is, in the manufacturing method of the hypereutectic Al-Si alloy casting of the present invention, it is extremely important that the hypereutectic Al-Si alloy contains 5 to 50 ppm of P and that the molten hypereutectic Al-Si alloy is heated to the crystallization temperature of the AlP compounds or higher. In addition, the content of P is preferably 20 to 40 ppm.

[0026] In the manufacturing method of hypereutectic Al-Si alloy castings of the present invention, the molten hypereutectic Al-Si alloy is held at 1050°C or higher for 5 minutes or more, so that the effect of refining AlP compounds can be fully exerted. The holding time is preferably 30 minutes or less. If the holding time is 30 minutes or less, the effect of refining AlP compounds is not lost, and an increase in energy consumption and deterioration of facilities such as a melting furnace can be suppressed. Effect of the Invention

[0027] According to the present invention, it is possible to easily and inexpensively increase the Si content to 17×10 -6 ℃ -1 The present invention provides a hypereutectic Al-Si alloy casting capable of exhibiting the following linear expansion coefficient, a hypereutectic Al-Si alloy that can be suitably used for the hypereutectic Al-Si alloy casting, and a simple and efficient method for producing the hypereutectic Al-Si alloy casting. [Brief description of the drawings]

[0028] [Figure 1] 1 shows microstructure photographs of aluminum alloy castings 1 to 4. [Diagram 2] 1 shows microstructure photographs of comparative aluminum alloy castings 1 to 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] The hypereutectic Al-Si alloy and hypereutectic Al-Si alloy casting of the present invention and the method for producing the same will be described in detail below, but the present invention is not limited to these alone.

[0030] 1.Hypereutectic Al-Si alloy The hypereutectic Al-Si alloy of the present invention is characterized by containing appropriate amounts of P and Ni. Each component will be described in detail below.

[0031] (1)Additional elements (1-1) Essential additive elements Si: 15.0-17.0wt% Silicon crystallizes as primary silicon or eutectic silicon, disrupts the α phase, and reduces the linear expansion coefficient. This effect of reducing the linear expansion coefficient is significant at 15.0 wt% or more. Silicon also improves castability, wear resistance, tensile strength, yield strength, wear resistance, and other mechanical properties, as well as chip separability. If the Si content exceeds 17.0 wt%, the crystallized material tends to become coarse. Coarsening of primary silicon not only deteriorates castability, but also causes a decrease in toughness and increased wear of cutting tools.

[0032] Ni: 3.0-5.0wt% Ni crystallizes as an Al-Ni compound, which breaks up the α phase and reduces the thermal expansion coefficient. It also contributes to improving heat resistance. This effect becomes more pronounced when added at 3.0wt% or more. Conversely, when added at 5.0wt% or more, the Al-Ni compound tends to coarsen, which may reduce toughness.

[0033] P: 5 to 50 ppm (preferably, 20 to 40 ppm) When P is added to molten aluminum, it forms AlP compounds that become the crystallization nuclei of primary Si, and contributes to the refinement of primary Si. This effect is remarkable at 5 ppm or more. On the other hand, when P is added in an amount exceeding 50 ppm, coarse AlP compounds are formed, and the eutectic Si tends to coarsen with the coarse AlP compounds as the crystallization nuclei, the division of the α phase becomes insufficient, and the effect of reducing the linear expansion coefficient is reduced. Furthermore, a reduction in toughness occurs. The preferable content of P is 20 to 40 ppm.

[0034] (1-2) Optional additive elements In order to refine the structure of the hypereutectic Al-Si alloy casting obtained by using the hypereutectic Al-Si alloy of the present invention, a refiner may be added.

[0035] As a refiner for the cast structure, one or more of Ti: 0.05-0.20wt%, B: 0.005-0.100wt%, and Zr: 0.05-0.20wt% can be added. The addition of Ti, B, and Zr refines the structure, which can mainly improve toughness. If the content is less than the lower limit, the effect is small, and even if the content exceeds the upper limit, the structure is already sufficiently refined and has no effect. In addition, if added excessively, coarse crystals are formed, which adversely affects ductility. Therefore, it is necessary to limit the content to the above range.

[0036] (1-3) Inevitable impurities Since recycled raw materials are often used for the hypereutectic Al-Si alloy of the present invention, the inclusion of unavoidable impurities is permitted within a range that does not impair the properties of the hypereutectic Al-Si alloy and hypereutectic Al-Si alloy castings of the present invention.

[0037] Cu has the effect of improving mechanical properties, but forms Al-Ni-Cu compounds that contribute less to the reduction in the linear expansion coefficient than Al-Ni compounds, thereby reducing the effect of adding Ni. Therefore, it is preferable to keep the content of Cu at 0.6 wt% or less.

[0038] Fe has the effect of improving mechanical properties, but Fe-based compounds turn into needle-like shapes and become the starting points of fracture when stress is applied, causing a decrease in toughness, so it is preferable to keep the content of Fe at 1.0 wt% or less.

[0039] Other impurities such as Mg, Mn, Cr, V, and Zn are permitted to be contained within a range that does not impair the properties of the hypereutectic Al-Si alloy and hypereutectic Al-Si alloy castings of the present invention, but it is preferable to restrict the content to 0.05 wt% or less.

[0040] 2. Hypereutectic Al-Si alloy castings The hypereutectic Al-Si alloy casting of the present invention is made of the hypereutectic Al-Si alloy of the present invention, and the linear expansion coefficient is reduced to 17×10 by controlling the microstructure (fine division of the α phase). -6 ℃ -1 The following features are characteristic of the hypereutectic Al-Si alloy castings. The microstructure of the hypereutectic Al-Si alloy castings will be described in detail below.

[0041] (1) Primary Si In the hypereutectic Al-Si alloy casting of the present invention, by containing 5 ppm or more of P, a large number of AlP compounds which become the nuclei of primary crystals during melting and solidification are formed, and a large number of fine primary crystals are simultaneously formed, suppressing the coarsening of the primary crystals. As a result, the average grain size of the primary crystals is 40 μm or less.

[0042] Here, the average grain size of primary crystal Si can be found as the circle-equivalent diameter. The circle-equivalent diameter is the diameter when the area occupied by primary crystal Si, found when observing the metal structure under a microscope, is converted into the area equivalent to a circle. Specifically, it can be easily found by subjecting a micrograph to image processing or the like. Since the contrast between the primary crystal Si region and other regions is clearly different on the micrograph, the image is binarized and then various image measurement processes are carried out. The average grain size is, for example, the diameter of the area within a certain visual field (measurement area: 1.3 mm 2 The average value of the circle equivalent diameter of the measurement field of view (number of measurement fields: 3) can be used.

[0043] (2) Eutectic Si In the hypereutectic Al-Si alloy casting of the present invention, by making the P content 50 ppm or less, the number of AlP compounds is not too large, and the formed AlP compounds are consumed by primary crystal Si, so that they hardly exist during eutectic solidification. As a result, the residual liquid during eutectic solidification is supercooled, the solidification time is shortened, and the coarsening of the eutectic is suppressed, and the average phase spacing of the eutectic Si is 20 μm or less.

[0044] The method for measuring the interlayer spacing of eutectic silicon is not particularly limited, and the measurement can be performed by various conventionally known methods. For example, the measurement can be performed using the intersection method of the dendrite arm spacing measurement procedure described in "Light Metals Institute, Casting and Solidification Division: Light Metals, 38 (1988) 54-60."

[0045] The method of observing the eutectic Si is not particularly limited as long as it does not impair the effects of the present invention, and various conventionally known methods can be used, for example, optical microscope observation or SEM observation. The eutectic Si region and other regions have clearly different contrast in the microscope photograph or SEM observation image, so they can be clearly distinguished.

[0046] (3) Other crystallized phases Since the hypereutectic Al-Si alloy of the present invention contains 3.0 to 5.0 wt% Ni, Al3Ni crystallizes in the hypereutectic Al-Si alloy casting. The Al3Ni crystallized particles tend to have a large aspect ratio, and can effectively divide the α phase.

[0047] (4)α phase The α phase is finely divided by the dispersion of fine primary Si, the reduction in the average spacing between adjacent eutectic Si, and the crystallization of Al3Ni. In addition, due to the fine division of the α phase, the linear expansion coefficient of the hypereutectic Al-Si alloy casting is 17×10 -6 ℃ -1 The details are as follows.

[0048] The shape and size of the hypereutectic Al-Si alloy casting of the present invention are not particularly limited as long as the effect of the present invention is not impaired, and may be any of various shapes and sizes conventionally known for aluminum alloy castings. Moreover, the hypereutectic Al-Si alloy casting of the present invention is not limited to those produced by a specific casting method such as heavy casting or die casting, and includes those produced by various conventionally known casting methods.

[0049] 3. Manufacturing method of hypereutectic Al-Si alloy castings The method for producing a hypereutectic Al-Si alloy casting of the present invention is characterized in that a molten aluminum alloy consisting of the hypereutectic Al-Si alloy of the present invention is held at a temperature of 1050°C or higher for 5 minutes or more, and then cast.

[0050] The crystallization temperature of AlP, which acts as the crystallization nucleus for primary Si, is approximately 950°C, and when the temperature is held at 1050°C or higher, the AlP melts once, and then when the temperature of the molten metal is lowered for casting, a large amount of fine AlP crystallizes, and then fine primary Si and eutectic Si crystallize from the fine AlP as crystallization nuclei. The fine crystallization of primary Si and eutectic Si finely divides the α phase, lowering the linear expansion coefficient of the hypereutectic Al-Si alloy casting.

[0051] By holding the molten hypereutectic Al-Si alloy at 1050°C or higher for 5 minutes or more, the effect of refining the AlP compounds can be fully exerted. The holding time is preferably 30 minutes or less. If the holding time is 30 minutes or less, the effect of refining the AlP compounds is not lost, and an increase in energy consumption and deterioration of facilities such as a melting furnace can be suppressed.

[0052] Other casting conditions are not particularly limited as long as they do not impair the effects of the present invention, and various conventionally known casting methods and casting conditions can be used.

[0053] Representative embodiments of the present invention have been described above, but the present invention is not limited to these, and various design modifications are possible, all of which are included in the technical scope of the present invention. EXAMPLES

[0054] Example Raw materials mixed to obtain the compositions shown in Examples 1 to 4 in Table 1 were placed in a graphite crucible, melted in air at 750°C, and then degassed at 750°C using a rotary degasser. The remaining molten metal was then heated to 1080°C in air and held for 10 minutes (molten metal superheating treatment), and then cast into a boat shape (JIS H 5202) by gravity casting to obtain the hypereutectic Al-Si alloy castings 1 to 4 of the present invention. The mold temperature was 150°C, and Cu and Fe were mixed in as unavoidable impurities within the allowable range.

[0055] [Table 1]

[0056] Comparative Example Comparative hypereutectic Al-Si alloy castings 1 to 5 were obtained in the same manner as in the Examples, except that the compositions shown in Comparative Examples 1 to 5 in Table 1 were used and Comparative Examples 1 and 2 were not subjected to molten metal superheating treatment.

[0057] [Evaluation test] (1) Microstructure A cube with a size of 1 cm on a side was cut out from the obtained example aluminum alloy castings and comparative aluminum alloy castings, centered at a position 13 mm from the bottom, and the cross section was buffed to prepare a sample for structure observation. The microstructures of the example aluminum alloy castings 1 to 4 and the comparative aluminum alloy castings 1 to 4 observed with an optical microscope are shown in Figures 1 and 2, respectively. The average grain size of primary crystal Si and the average interphase spacing of eutectic Si measured from these observation results are also shown in Table 1.

[0058] In all of the hypereutectic Al-Si alloy castings, the primary Si crystals are refined and the average interphase spacing of the eutectic Si crystals is reduced, with the average grain size of the primary Si crystals being 40 μm or less and the average interphase spacing of the eutectic Si crystals being 20 μm or less.

[0059] On the other hand, the average interphase spacing of eutectic Si is large, exceeding 20 μm, in comparative hypereutectic Al-Si alloy castings 1 and 2, which were not subjected to molten metal superheating treatment. Also, it can be seen that the primary Si crystals become coarse in comparative hypereutectic Al-Si alloy casting 4, which has a high Si content, even when molten metal superheating treatment was performed.

[0060] (2) Linear expansion coefficient measurement The average linear expansion coefficient of each aluminum alloy casting was measured from 30 to 150°C by a push rod type thermal expansion meter. Specifically, an aluminum alloy test piece with a diameter of 10 mm and a length of 50 mm was heated. The change in elongation of the rod-shaped sample was transmitted to a differential transformer by a detection rod, converted in direct proportion to the change in voltage, and recorded on a recorder together with the sample temperature. The heating rate was 2°C / min. The results are shown in Table 1.

[0061] All hypereutectic Al-Si alloy castings have a linear expansion coefficient of 17×10 -6 ℃ -1 In contrast, the linear expansion coefficients of comparative hypereutectic Al-Si alloy castings 1 and 2, which were not subjected to molten metal superheat treatment and had a large eutectic Si interval, comparative hypereutectic Al-Si alloy casting 3, which had a low Si content and did not obtain the effect of dividing the α phase due to primary crystallized Si and eutectic Si, and comparative hypereutectic Al-Si alloy casting 5, which had a low Ni content and did not obtain a sufficient effect of dividing the α phase due to Al3Ni crystallized substances, were 17 × 10 -6 ℃ -1 Here, the linear expansion coefficient of comparative hypereutectic Al-Si alloy casting 4 is 17 × 10 -6 ℃ -1 However, due to the high Si content, the primary Si crystals are coarse, making it difficult to use the material as a structural member that requires reliability.

Claims

1. Si: 15.0-17.0wt%, Ni: 3.0 to 5.0 wt%, P: 5 to 50 ppm; The balance is composed of Al and inevitable impurities. A hypereutectic Al-Si alloy characterized by:

2. The hypereutectic Al-Si alloy according to claim 1, The average grain size (equivalent circle diameter) of primary crystal Si is 40 μm or less, The average spacing between adjacent eutectic Si is 20 μm or less; Linear expansion coefficient is 17 x 10 -6 ℃ -1 That is: A hypereutectic Al-Si alloy casting characterized by:

3. A 3 Ni is crystallized, The hypereutectic Al-Si alloy casting according to claim 2,

4. The molten aluminum alloy made of the hypereutectic Al-Si alloy according to claim 1 is held at a temperature of 1050°C or higher for 5 minutes or more, and then cast. A method for producing a hypereutectic Al-Si alloy casting, comprising the steps of:

Citation Information

Patent Citations

  • Al alloy material having low coefficient of linear expansion

    JP1987056551A

  • Low thermal expansion aluminum alloy sheet material having excellent proof stress, and method for producing the same

    JP2009263720A

  • Method for producing aluminum alloy

    JP2011255392A

  • HYPEREUTECTIC Al-Si ALUMINUM ALLOY, AND CAST MEMBER COMPRISING THE SAME, AND METHOD FOR PRODUCING ALUMINUM ALLOY

    JP2017119890A

  • Method for making alp compounds finer and aluminum alloy casting

    JP2020152996A